HBV/HIV co-infection and APOBEC3G polymorphisms in a population from Burkina Faso. Issue 1 (December 2016) - Compaore, Tegwinde; Diarra, Birama; Assih, Maleki; Obiri-Yeboah, Dorcas; Soubeiga, Serge; Ouattara, Abdoul; Tchelougou, Damehan; Bisseye, Cyrille; Bakouan, Didier; Compaore, Issaka; Dembele, Augustine; Djigma, Wendkuuni; et al.
Abstract Background Apolipoprotein B mRNA editing enzyme catalytic polypeptide-like 3G (APOBEC3G) is a potent host defense factor, which interferes with HIV-1 and HBV. Our study had three objectives, to screen a population of HIV-1 infected and uninfected patients in Burkina Faso for HBV, to screen the population for APOBEC3G variants rs6001417, rs8177832, and rs35228531 previously described, and to analyze the effect of these three variants and their haplotypes on HIV-1/HBV co-infection in Burkina Faso. Methods HBV detection was performed on samples from HIV-1 infected and uninfected subjects using rapid detection tests and real-time PCR. APOBEC3 genotyping was done by the TaqMan allelic discrimination method. Fisher Exact test, Odds ratio (OR), confidence intervals (CI) at 95 %, Linkage disequilibrium (LD) summary statistics and haplotype frequencies were calculated. Results The prevalence of HBV was 56.7 % among HIV-1 positive patients of our study while it was about 12.8 % among HIV-1 seronegative subjects. Genotype E was the genotype of HBV present in our hepatitis B positive samples. Minor allele frequencies of rs6001417, rs8177832, and rs35228531 were higher in seronegative subjects. The T minor allele of variant rs35228531 was protective against HIV-1/HBV co-infection with OR = 0.61, 95 % CI (0.42–0.90), p  = 0.013. There was also an association between the GGT haplotype and protection against HIV-1/HBV co-infection, OR = 0.57, 95 % CI (0.33–0.99), p  = 0.050. The other haplotypes present in the population were not statistically significant. There minor allele T of the rs35228531 was protective against HIV mono-infection OR = 0.53, 95 % CI (0.3–0.93), P  = 0.030. But there was no effect of protection against HBV mono-infection. Conclusion APOBEC3G through its variants rs6001417, rs8177832, and rs35228531, in this study interferes with HIV-1/HBV co-infection could be due the HIV-1 mono-infection in a population from Burkina Faso.